De biënnale van de een minuten. - Binshtock, Tammuz; Brink, Yaron ten; Dallch, Efrat; Ex, Sjarel; Groner, Sagi; Hallberg, Peter; Houweling, Jos; Smallenburg, Sandra; Tuinder, Dick; Van Beek, Nils; Exhibition. De biënnale van de een minuten. Centraal Museum Utrecht. Sandberg Instituut. 2002-05-30. 2002-06-02 (Amsterdam : De Verenigde Sandbergen, 2002)
Zwaan, Nicky ; Thijsen, Alite ; Käppler, Sabine ; Fliervoet, Maartje ; Butink, Michal ; Taudin Chabot, Raymond ; Lukacs, Margit ; Broersen, Persijn ; Messieurs Delmotte ; Rouppe van der Voort, Alexandra ; Vlasman, Petra ; Weelinck, Robert ; Schaap & Timmer ; Donkers, Nell ; Hymoller, Kristine ; Bagge, Thomas ; Helbo, Gunver ; Lyshoj, Helle ; Sejbjerg, Tina ; Dick, Helmut ; Göttke, Florian ; Kratz, Stephanie ; Maurer, Luna ; Hero, Kathrin ; Niefeld, Hendrik ; Mandon, Thierry ; Brun, Denis ; Hasé, Karin ; X-off ; Spijker en splinter ; Riviera, Lara ; Epstein, Jill ; Konti, Maria ; Migkos, Adonis ; Mouzaki, Aimilia ; Nymfiada, Maria ; Petratou, Kiki ; Pittas, Antonis ; Schina, Maria ; Tsivopoulos, Stefanos ; Zervou, Maria ; Coenen, Arno ; Björgulfsson, Heimir ; Reynisdottir, Gigia ; Thorsson, Helgi ; Logi Kristinsson, Magnus ; de Michele, Alberto ; Dallch, Efrat ; Steinberg, Eti ; Kadman, Hadar ; Peled, Nirit ; Nitzan, Roiy ; Pront, Ron ; Groner, Sagi ; Binshtock, Tammuz ; Drukman, Uri ; Love, Uri ; Brink, Yaron ten ; Cohen, Shani ; Yoshimura, Ayako ; van Stiphout, Ivo ; Inatome, Kyoko ; Masayuki, Watanabe ; Takamine, Tadasu ; Kimura, Yuki ; Pastrana, Elizabeth ; Coelho, Ramon ; Graham, Dylan ; Verhoysen, Anne ; Djindikhachvili, David ; Mizin, Slava ; Bardic, Dario ; Kielczynska, Kinga ; Mormil, Marko ; Stojadinovic, Vava M. ; Piek! ; Schrikker, Simon ; Zoetman, Allard ; Span, Renée W. ; Bakker, Ineke ; Smarius, Stefan ; Joose, Tessa ; Ning, Bei ; Evers, Marissa ; Hansson, Lena ; Monfeldt, Magnus ; Perborg, Björn ; Strömberg, Pär ; Säfve, Etta ; Wergius, Pia ; Busslinger, Erich ; Nyboer, Erwin ; Wyss, Sonja ; Daubé, Mir ; Mooibroek, Sabine
Nederlands
boek